2020
DOI: 10.1016/j.heliyon.2020.e03229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of packaging and duration on quality of minimally processed and unpitted litchi cv. ‘Mauritius’ under low storage temperature

Abstract: Pericarp drying is a major postharvest challenge affecting the shelf life of litchi fruit resulting in loss of market value and consumer rejection. Sulphur dioxide (SO 2 ) is considered an allergen due to its ability to cause irritation in people, particularly those vulnerable to asthma. Thus, the objective of this study was to investigate the effects of packaging and storage duration without SO 2 on the quality attributes of minimally processed litchi fruit cv. 'Mauritus'. Minimally processed litchi cv. 'Maur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 39 publications
2
22
2
Order By: Relevance
“…As a result, food preservation is a huge challenge in the whole world. In order to extend the shelf-life of food, a variety of physical, chemical and biological techniques, including low-temperature storage, controlled atmosphere storage, heat treatment, irradiation treatment and the use of preservatives have been used [ 3 , 4 , 5 , 6 ]. In the last decade, alternative food preservative techniques have emerged, considered as promising alternatives to gradually replace the traditional preservation process, especially films with a certain function in food packaging, which has become the research hotspot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, food preservation is a huge challenge in the whole world. In order to extend the shelf-life of food, a variety of physical, chemical and biological techniques, including low-temperature storage, controlled atmosphere storage, heat treatment, irradiation treatment and the use of preservatives have been used [ 3 , 4 , 5 , 6 ]. In the last decade, alternative food preservative techniques have emerged, considered as promising alternatives to gradually replace the traditional preservation process, especially films with a certain function in food packaging, which has become the research hotspot.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the tensile strength of a starch film added with cellulose was increased by 18 times, and the water vapor transmission ratio was reduced compared with the starch film without cellulose. Riaz et al [ 3 ] found that blending pectin and chitosan at a ratio of 1:1 increased tensile strength, reduced water solubility, water vapour permeability and oxygen permeability. Therefore, pectin and chitosan composites could be used as a film matrix to improve the tensile strength and barrier properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this investigation the longest market life of litchi fruit at 5 ± 1ºC for 30 days as compared to the storage at ambient condition. However, the main postharvest challenges such as pericarp browning, dehydration, decay, loss of quality, flavor, and shelf life during the storage period (Mphahlele et al, 2020). The postharvest management strategies and novel technologies i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Flower senescence was also closely related to membrane permeability ( Wang, 1990 ). Increased membrane permeability led to petal senescence, loss of turgor, and visible wilting due to higher cellular electrolyte leakage ( Mphahlele et al., 2020 ; Faragher et al., 1987 ). According to Leverentz et al.…”
Section: Resultsmentioning
confidence: 99%